Beneficial Effects of the β-Secretase Inhibitor GRL-8234 in 5XFAD Alzheimer’s Transgenic Mice Lessen During Disease Progression - Devi, Latha; Tang, Jordan; Ohno, Masuo (Current Alzheimer Research, 2015)
The β-secretase enzyme BACE1, which initiates the cleavage of amyloid precursor protein (APP) into the amyloid-β (Aβ) peptide, is a prime therapeutic target for Alzheimer’s disease (AD). However, recent investigations using genetic animal models raise concern that therapeutic BACE1 inhibition may encounter the dramatic reduction of efficacy in ameliorating AD-like pathology and memory deficits during disease progression. Here, we compared the effects of the potent and selective small-molecule BACE1 inhibitor GRL-8234 in different pathological stages of AD mouse model. Specifically, we administered GRL-8234 (33.4 mg/kg, i.p.) once daily for 2 months to 5XFAD transgenic mice, which showed modest (4 months) and massive (10 months of age) Aβ plaque deposition at starting points. Chronic treatments with GRL-8234 reversed memory impairments, as tested by the spontaneous alternation Y-maze task, in the younger 5XFAD group concomitant with significant reductions in cerebral Aβ42 levels. In contrast, only marginal reductions of Aβ42 were observed in 12-month-old 5XFAD mice treated with GRL-8234 and their memory function remained impaired. We found that not only BACE1 but also full-length APP expression was significantly elevated with progressive Aβ accumulation in 5XFAD mice, while GRL-8234 failed to affect these detrimental mechanisms that further accelerate plaque growth in brains of older 5XFAD mice. Therefore, our results provide important insights into the mechanisms by which Aβ accumulation and related memory impairments become less responsive to rescue by BACE1 inhibition during the course of AD development.
Keywords: Alzheimer’s disease